41 years since the adoption of the United Nations Convention on the Law of the Sea - Anechitoae, Constantin (Eximia, 2023)
The United Nations Convention on the Law of the Sea signed on 10.12.1981 – Montego-Bay, Jamaica, made an important contribution to the universally accepted delimitation of the territorial sea, the contiguous zone, the exclusive economic zone and the continental shelf which led to a significant contribution on human well-being, in terms of commercial and non-commercial resources. The codification of the law of the sea is one of the most significant achievements of the Montego Bay Convention. Also, an important role was the protection of the economic interests of all landlocked or landlocked countries, with a particular concern for the protection and preservation of the marine environment and marine fauna but also the protection of biological resources. The provisions of the Convention led to the start of many international debates - for the elaboration of a specific legal status, on the maritime spaces but also on the spaces adjacent to the territorial sea.